Cultural Issues and Teaching Literature for Language Learning - Nasirahmadi, Arman; Madarsara, Fatemeh Alipour; Aghdam, Hamed Rezapour (Elsevier Science Bv, 2014)
The aim of this study was to investigate the effectiveness of incorporating culturally-loaded materials like literature in EFL courses. We selected short story as an example of literature to be included in our course syllabus. After that, some eclectic short stories from Chicken Soup for the Soul were selected. 14 students were randomly selected and assigned to two classes as control group and experimental groups. Finally, by comparing the mean and median of their final scores, we found that the experimental group outperformed the control group both in the final exam and also during the term considering classroom discussions. (C) 2014 The Authors. Published by Elsevier Ltd. Open access under CC BY-NC-YD
International Conference on Current Trends in ELT - Putting the Learner in the Spotlight -- MAY 20-22, 2013 -- Urmia Univ, Urmia, IRAN
Keywords: culture; literature; short story; EFL courses; EFL learners; experimental group; control group